PD-L1 alternative splicing - Zhen, Yashu (Nanyang Technological University, 2022)
PD-L1 is an immune checkpoint molecule which is upregulated in some tumors to evade the immune response. Generation of truncated and nonfunctional PD-L1 variants by modulation of alternative splicing presents a novel strategy for cancer treatments. PD-L1 alternative splicing was studied using minigenes, to identify a splicing silencer inside Exon 4 exonic intron (exitron) which represses the splicing of this exitron. Besides, this splicing event seems to require the 5’ss splice site of Exon 4, and it is also negatively regulated by SRSF1 and the 3’ss splice site of Exon 6.